Epidemiology of multi-resistance Gram negative pathogen circulating in Liguria and molecular characterization of different carbapenemases - Erika Coppo; Ramona Barbieri; Paolo Piazzai; Andrea Dusi; David Usiglio; Marco Mori; Roberto Bandettini; Agostina Ronca; Luisa Santoriello; Domizio Serra; Silvia Reali; Anna Marchese; et al. (Microbiologia Medica, 2011)
This study was conducted during January-April 2010 with the collaboration of 7 clinical microbiology laboratories evenly distributed across the Ligurian area to identify the most frequent Gram negative species and to evaluate their antibiotic susceptibility patterns Overall, 110 consecutive multi-resistant non duplicate Gram negative isolates,were collected and sent to the coordinating laboratory (Sezione di Microbiologia del DISC, University of Genoa, Italy) together with susceptibility data obtained by routine methods. In addition, strains resistant to carbapenems were characterized by PCR. A total of 110 Gram negative multi-resistance strains were found, including 74 and 36 isolated from healthcare or nosocomial settings and community acquired infections, respectively. The most represented pathogens were: A. baumannii (38, 34.5%), E. coli (30, 27.2%), P. aeruginosa (29, 26.3%), K. pneumoniae (9, 8.2%) and P. mirabilis (4, 3.6%). A. baumannii were more frequently collected from healthcare settings or nosocomial samples, while the other strains were generally equally isolated from in- and out-patients. Amikacin was the most active molecule against E. coli and P. mirabilis (96,7% and 100% of susceptible stains respectively). Colistin was the only active molecule agains A. baumanii and P. aeruginosa (100% of susceptible strains). Against K. pneumoniae tigecycline and colistin were the most active molecules (100% of susceptible strains). Imipenem was the most active compound against E. coli and P. mirabilis (100% of susceptible strains). A large number (97.4%) of A. baumannii was resistant to imipenem. K. pneumoniae and P. aeruginosa showed rates of resistance of 88% and 34.4% respectively. A. baumannii, K. pneumoniae and P. aeruginosa isolates resistant to Imipenem, carried OXA-23, KPC and VIM carbapenemases.These data shown a significant spread of multidrug-resistant Gram negative bacteria in hospitals and in communities.The production of carbapenemase in A. baumannii, K. pneumoniae and P. aeruginosa is now an important phenomenon in our region.